2015
DOI: 10.13170/aijst.4.3.3017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fe-intercalated Graphite Based on Coal Tailings, Dimensional Structure

Abstract: <p>Intercalated graphite from coal tailings have been modified through the intercalation of iron. Coal tailings which is a byproduct of the destruction process and flakes washing results from mining coal. Intercalation of iron goal is to improve the physical properties of graphite and modifying sizes of crystal lattice structure with thermal method. Modification process begins with the carbonization of coal tailings at 500ºC and activated with phosphoric acid. Activation process has done by pyrolysis at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The previous study has reported that conductivity composite membranes based on sulfonated polysulfone and activated carbon has been measured as 8.8 x 10 -4 S/cm at 40 °C. 17 The conductivity isotherm illustrates that the DC conductivities of SPSU-NZ composite membranes strongly depend on temperature as well as on the mass ratio of NZ. However, the DC conductivity illustrates that the NZ content increases the conductivity for SPSU-NZ: 1:0.5 composite membrane, and decreases the conductivity for SPSU-NZ; 1:1.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The previous study has reported that conductivity composite membranes based on sulfonated polysulfone and activated carbon has been measured as 8.8 x 10 -4 S/cm at 40 °C. 17 The conductivity isotherm illustrates that the DC conductivities of SPSU-NZ composite membranes strongly depend on temperature as well as on the mass ratio of NZ. However, the DC conductivity illustrates that the NZ content increases the conductivity for SPSU-NZ: 1:0.5 composite membrane, and decreases the conductivity for SPSU-NZ; 1:1.…”
Section: Resultsmentioning
confidence: 96%
“…17 Compared with the sulfonated spectrum, there is the difference. Differences in the spectrum of sulfonated polysulfone and polysulfone are particularly apparent in the area of the wavelength number 3700-2900 cm -1 and near the region 1310-1200 cm -1 , where the polysulfone spectrum does not show the vibration of the OH strain and the symmetry O = S = O of the cluster sulfonate -SO3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polysulfone (PSf) has excellent chemical resistance almost an entire range of pH (2-13) and oxidative medium (5-7% hypochlorite, hydrogen peroxide 3-5%). [26][27][28][29][30] However, PSf tends to form symmetry structures with high mass transfer resistance so that the fouling tendency becomes higher than the asymmetric membrane. In addition, the PSf membrane has a characteristical structure with large pore diameter but with a highly porous layer thickness.…”
Section: Introductionmentioning
confidence: 99%